Novel 4-Thiazolidinones as Non-Nucleoside Inhibitors of Hepatitis C Virus NS5B RNA-Dependent RNA Polymerase - TATAR, ESRA; KÜÇÜKGÜZEL, İLKAY (WILEY-V C H VERLAG GMBH, 2015)
In continuation of our efforts to develop new derivatives as hepatitis C virus (HCV) NS5B inhibitors, we synthesized novel 5-arylidene-4-thiazolidinones. The novel compounds 29-42, together with their synthetic precursors 22-28, were tested for HCV NS5B inhibitory activity; 12 of these compounds displayed IC50 values between 25.3 and 54.1 mu M. Compound 33, an arylidene derivative, was found to be the most active compound in this series with an IC50 value of 25.3 mu M. Molecular docking studies were performed on the thumb pocket-II of NS5B to postulate the binding mode for these compounds.
Keywords: Antiviral agents; Hepatitis C; HCV NS5B polymerase; Molecular modeling; 4-Thiazolidinones; ANTIMICROBIAL ACTIVITY; BIOLOGICAL EVALUATION; DESIGN; THIOSEMICARBAZONES; PHARMACOPHORE; DERIVATIVES; THIAZOLIDINONES; IDENTIFICATION; RESISTANCE; DISCOVERY